Effect of "Jian-Pi-Zhi-Dong Decoction" on Gamma-Aminobutyric Acid in a Mouse Model of Tourette Syndrome. (9th April 2014) - Zhang, Wen; Yu, Wenjing; Wang, Daohan; Wei, Li; Lee, Minkyoung; Wang, Sumei
Abstract : The purpose of this study was to explore the positive effects of Jian-Pi-Zhi-Dong Decoction (JPZDD) on Tourette syndrome (TS) by investigating the expression of gamma-aminobutyric acid (GABA) and its type A receptor (GABAA R) in the striatum of a TS mice model. The model was induced by 3, 3′-iminodipropionitrile (IDPN) treatment; then mice were divided into 4 groups (n=22, each); control and IDPN groups were gavaged with saline and the remaining 2 groups were gavaged with tiapride and JPZDD. We recorded the stereotypic behaviors of TS mice and measured the content of GABA in striatum by HPLC and GABAA R expression by immunohistochemistry and real-time PCR. Our results showed that JPZDD inhibited the abnormal behaviors of TS model mice and decreased GABA levels and GABAA R protein and mRNA expression in the striatum of TS model mice. In brief, the mechanism by which JPZDD alleviates TS symptoms may be associated with GABAA R expression downregulation in striatum which may regulate GABA metabolism.